Impact of Guidance and Counselling Services on Academic Performance of Students in Some Selected Secondary Schools in Sokoto Metropolis - Ibrahim, Shehu; Bandi, Iklima Ibrahim; Danyaya, Jabir Aliyu; Sahabi, Mustapha; Abubakar, Ibrahim (International Journal of Applied Guidance and Counseling, 2021)
The study aims to evaluating the impact of guidance and counseling services on the academic performance of students in some selected secondary schools in Sokoto metropolis. Causal-comparative (Ex-post facto) research design was adopted for this study. This study involves a total of 200 subjects comprising 5 principals, 25 class teachers, 10 teacher counselors, and 160 students from the five selected schools. Data were collected using the four sets of questionnaires. Data analysis was done using descriptive and inferential statistics. The finding revealed that eighty percent (80%) of the students responded that their academic performance was changed after receiving counseling services. Seventy-two percent (72%) of the class teachers perceived the level of students’ academic performance after counseling as good, while 20% perceived it very good and 8% rated it bad. Guidance and counseling services have positively influenced the academic performance of the students and should be strengthened to improve the students’ performance in national examinations.